Critical thinking skills for diagnosis process application from the perspective of nursing students and professors (Acta Scientiarum. Health Sciences, 2020)
Identify, from the experiences of nursing students and their professors, the critical thinking skills necessary for applying the diagnosis process to clinical practice. Descriptive-exploratory with qualitative approach. The study was conducted at a higher education institution in the south of Brazil, after approval from the Research Ethics Committee, under CAEE No 72294917.7.0000.5347. It had the participation of five nursing students and four nursing professors through focal group sessions. The content analysis technique was used for data analysis. The most remarkable holistic critical thinking skills identified from the point of view of the nursing students were: analysis and knowledge; from the professors' perspective, they were: analysis, information search, clinical experience, knowledge transformation, contextual perspective, intuition, prediction and comprehension. With the findings of this research, professors will be capable of implementing strategies focused on the individual needs of students in order to qualify teaching practices as to the nursing diagnosis process.